Raman spectroscopy study of glass corrosion - Hruska, Branislav; Gavenda, Tadeas; Vasicek, Filip; Svoboda, Roman (Elsevier Science BV, 2020)
Binary sodium silicate and potassium silicate glasses with different alkali content were exposed to the corrosion environment of 35 % hydrochloric acid (HCl). Glass samples were measured by Raman spectroscopy and the spectra were compared with Raman spectra of original pristine glasses in order to observe structural changes induced by corrosion within the surface layer. The usage of confocal Raman spectroscope enabled the measurement of Raman spectra from the depths of few micrometres to document the range of structural changes. The results suggest the depolymerisation of silicate structure due to the growth of the corrosion layer on the surface. The decrease of D2 peak points at the decomposition of three-membered rings. In addition, it is assumed that the Si-O-Si angle changes within the surface layer.
Ramanova spektroskopická studie koroze skel
Keywords: alkali silicate glass; Raman spectroscopy; corrosion; glass surface; glass structure; silikátová skla; Ramanova spektroskopie; koroze; skelný povrch; skelná struktura